My Brother Has A Hearıng Loss: A Life Story Investigation - Osman Çolaklıoğlu; Zerrin Turan; Yıldız Uzuner (Anı Publishing, 2019)
The aim of this study, is to examine the life story of an adult who has a brother with hearing loss and to understand the effect of his brother on his life. The study designed as life story investigation. Data were collected through semi-structured interviews, reflective journals and documents. The data were analyzed using the inductive method. Research findings indicated that: The research participant Ahmet evaluated the effect of his brother with hearing loss on his own life differently at different periods of his life. His brother has no responsibility for his care and education, his parents do not treat his siblings with hearing loss, Ahmet says that his brother can live a life like everyone else with the rapid development of language development after the implant application. Ahmet saw the most negative effect of his brother's hearing loss on his life during his childhood as change the city where he lives. Today, however, he thinks that this situation actually has led to positive results his life.